Record Low Antarctic Sea Ice Cover in February 2022. Issue 12 (14th June 2022) - Turner, John; Holmes, Caroline; Caton Harrison, Thomas; Phillips, Tony; Jena, Babula; Reeves‐Francois, Tylei; Fogt, Ryan; Thomas, Elizabeth R.; Bajish, C. C.
Abstract: On 25 February 2022 Antarctic sea ice extent dropped to a satellite‐era record low level of 1.92 × 10 6  km 2, 0.92 × 10 6  km 2 below the long‐term mean. The area of sea ice was also at a record low level of 1.24 × 10 6  km 2 . Although no individual sector was at a record low, at the minimum there were negative sea ice anomalies in all sectors of the Southern Ocean, with the largest in the Ross (contributing 46%) and Weddell Seas (26%). The Amundsen Sea Low had a record low depth in October/November 2021, with a series of very deep depressions giving strong offshore winds. These accelerated ice loss during the melt season, creating a 1.00 × 10 6  km 2 coastal polynya in the Ross Sea. In the northern Weddell Sea, westerly winds of record strength led to ice export from the region. Plain Language Summary: Sea ice is a critical part of the Antarctic climate system that is an important breeding habitat for seals and other marine biota, as well as playing an important part in the global ocean circulation. Unlike the Arctic, where sea ice extent has decreased over recent decades, sea ice around the Antarctic actually increased in extent for a large part of the record starting in the late 1970s. However, on 25 February 2022 the extent dropped to a record low level of 1.924 million square kilometers, 1 million square kilometers below the long‐term average. The origins of the sea ice loss can be traced back to extremely deep storms in the Ross Sea in October and November 2021, and the very strong southerly winds that the storms had on their western flank. These moved sea ice away from the Antarctic coast, exposing the ocean and allowing solar heating to warm the ocean and give further sea ice melt. An additional factor was the very strong westerly winds north of the Weddell Sea that moved sea ice out of this basin and toward the east. Key Points: Antarctic sea ice extent dropped to a record low level of 1.92 × 10 6  km 2 on 25 February 2022 There were negative sea ice anomalies in all sectors of the Southern Ocean, with the largest in the Ross and Weddell Seas Deep storms in October/November 2021 led to low sea ice concentration and a large coastal polynya that accelerated sea ice loss